Role Of Nurses In Chronic Disease Management In Saudi Arabia (The Review of Diabetic Studies, 2024)
Introduction: A major problem for the health system of Saudi Arabia is the increasing number of chronic, non-communicable diseases. Some chronic, non-communicable diseases include Type 2 diabetes and cardiovascular disease. As part of the Health Sector Transformation Program of Saudi Vision 2030, a move away from providing acute care in hospitals and to providing chronic disease management (CDM) through primary care is being implemented. A major part of this change will be the change in the nursing role from that of a clinical assistant who supports physicians, to that of an independent manager of chronic disease.Objective: The goal of this systemic review is to gather together all evidence about how nurses work in managing Long-Term Conditions in the Health System of the Kingdom of Saudi Arabia according to Saudi Vision 2030.Method: A systematic search was performed on multiple electronic databases including PubMed, CINAHL, Scopus and the Saudi Digital Library to locate peer-reviewed studies published from 2020 through 2026. The studies selected for inclusion in this review were limited to those that pertain to nursing led chronic disease management within the Saudi context, using PRISMA guidelines.Conclusion: Nurses will play an integral role in the successful management of chronic diseases in Saudi Arabia. In addition to their roles in education, monitoring, and coordination of care, nurses support the Goals of Saudi Vision 2030 by reducing the number of hospitalizations and improving the overall health of the population. Efforts to continue to optimize the ability of nurses to have the greatest impact will be most effective if healthcare policy continues to prioritize creating more nursing jobs through the Saudization process and formalizing the clinical autonomy of Specialized Nurses.